Perancangan Aplikasi Cepat Tanggap Masayarakat Kecamatan Kota Ternate Utara - Aryan Alfabrian Jusuf (Manajemen Informatika, Akademi Ilmu Komputer Ternate, 2023)
The improvement of services and to promote performance in the District of North Ternate City is greatly influenced by the processing of its service system. So far, the processing of the service system at the North Ternate City District office is still using the manual method where what employees do in responding to public servants is still using the manual method. This study discusses the process of designing a Quick Response Application for the District of North Ternate City based on Android, quickly and easily in helping to provide services. With the use of the database system is expected to record the data that has been inputted and arranged properly in one database file. Keywords: Quick Response Community Application, North Ternate District Office, Android Based